Daily life participation in PTSD: pilot study on patterns and correlators - Shapira, Ruth; Baris Ginat, Yisca Jessica; Lipskaya-Velikovsky, Lena (Frontiers in Psychiatry, 2024)
Introduction Participation in daily life activities with both the personal and community meaning is an important component of health and well-being. Even though there are mounting reports on the challenges in various aspects of daily-life functioning among individuals with post-traumatic stress disorder (PTSD), to date little research has been conducted on their comprehensive patterns of participation. The study aimed to describe objective and subjective participation dimensions in PTSD compared to healthy controls and investigate the association between personal and environmental factors and participation. Methods Sixty-one individuals were enrolled in two groups: PTSD (N=31; age: M=34.3; women:77.4%) and healthy controls matched by age and gender. The PTSD group completed standard assessments for symptom severity, general cognition, executive function (EF), sensory processing, self-efficacy, functional capacity, and environmental properties. Both groups completed a participation questionnaire. Results Individuals with PTSD participated with low intensity and diversity, more occupations were abandoned (-4.73<t<5.73, p<0.05), and less meaning was found in the included occupations. Participation objective dimensions were associated with self-reported EF (-0.47<r<-0.42, p<0.05), sensory modulation profile (2.51<t<2.81, p<0.05), and environmental properties (-0.44<r<0.5, p<0.05), but not with PTSD symptom severity, and objective measures of cognition and functional capacity. No correlators were identified for subjective participation dimensions. Discussion The study demonstrates profound restrictions in participation in PTSD raising serious concerns. There are unique patterns of association between objective participation dimensions, subjective cognitive indices, sensory modulation, and environmental factors, suggesting a need for PTSD feature-specific intervention approaches to advance the participation of those with PTSD as a means of promoting health and well-being.